Asymmetric Michael Reaction of Malononitrile and α,β-Unsaturated Aldehydes Catalyzed by Diarylprolinol Silyl Ether - Hayashi, Yujiro; Hatano, Yutaro; Mori, Naoki (Synlett, 2022)
An asymmetric Michael reaction of malononitrile and α,β-unsaturated aldehydes catalyzed by a diarylprolinol silyl ether was developed. Michael products were obtained in good yields and with excellent enantioselectivities without the formation of overreaction products. As a malononitrile moiety can be transformed into an alkoxy or amino carbonyl moiety by oxidative transformation, α-chiral esters or amides with all-carbon quaternary centers can be synthesized with excellent enantioselectivities.
Keywords: organocatalysis; Michael reaction; asymmetric catalysis; diarylprolinol silyl ethers; malononitrile; carbon quaternary centers